Recurrent Parotid Carcinosarcoma in an Asymptomatic Patient - Joshua Mansour MD; Abhishek Mangaonkar MBBS; Vamsi Kota MBBS (SAGE Publishing, 2016)
In this article, we present the case of a 52-year-old male with a history of parotid carcinosarcoma with initial diagnosis being 18 months prior. Initial treatment included a combination of gamma knife surgery coupled with high dosage chemotherapy and X-ray radiation therapy. At the time of follow-up, the patient presented with no complaints and had a nearly normal physical exam with the exception of some facial nerve weakness on the same side as the initial surgery. Despite being asymptomatic, the patient had a significant progression of disease that was manifested with intracranial lesions, multiple pathologic fractures, and a dramatic increase in overall tumor burden. Ultimately, the patient decided to pursue comfort measures only and succumbed to the disease peacefully soon thereafter.